Tree growth inference and prediction when the point of measurement changes: modelling around buttresses in tropical forests - Metcalf, C; Clark, J; Clark, D (2009)
Estimation of tree growth is generally based on repeated diameter measurements. A buttress at the height of measurement will lead to overestimates of tree diameter. Because buttresses grow up the trunk through time, it has become common practice to increase the height of measurement, to ensure that measurements remain above the buttress. However, tapering of the trunk means that increasing measurement height will bias estimates of diameter downward by up to 10% per m of height. This bias could affect inference concerning species differences and climate effects on tree demography and on biomass accumulation. Here we introduce a hierarchical state space method that allows formal integration of data on diameter taken at different heights and can include individual variation, temporal effects or other covariates. We illustrate our approach using species from Barro Colorado Island, Panama, and La Selva, Costa Rica. Results include trends that are consistent with some of those previously reported for climate responses and changes over time, but differ in relative magnitude. By including the full data-set and accounting for bias and variation among individuals and over time, our approach allows for quantification of climate responses and the uncertainty associated with measurements and the underlying growth process. © 2008 Copyright Cambridge University Press.